2009
DOI: 10.1501/sbfder_0000002139
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Budget Participation on Managerial Performance via Organaizational Commitment:a Study on the Top 500 Firms in Turkey

Abstract: Bu çal mada örgütsel ba k arac yla bütçe kat n yönetsel performans nas l etkiledi i incelenmektedir. Bu ili kiyi test etmek için veriler, 2006 y nda Türkiye'de ilk be yüz büyük i letme içerisinde yer alan 150 firman n muhasebe-finansman yöneticilerinden, anket formu kullan larak elde edilmi tir. Verilerin analizinde tan mlay istatistik (ortalama ve standart sapma), korelasyon analizi, faktör analizi, regresyon analizi ve t-test analizi kullan lm r. Çal man n sonuçlar , yüksek performansl orta kademe yöneticile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(5 reference statements)
1
2
1
Order By: Relevance
“…Meanwhile, in the context of public sector organizations, budget goal commitment failed to prove its mediating role. In general, the relation between budget congruence and managerial performance is in line with the findings of Melek (2009) and Venkatesh & Blaskovich (2012), which state that participatory budgeting is an important factor for improving managerial performance. This study has several limitations.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Meanwhile, in the context of public sector organizations, budget goal commitment failed to prove its mediating role. In general, the relation between budget congruence and managerial performance is in line with the findings of Melek (2009) and Venkatesh & Blaskovich (2012), which state that participatory budgeting is an important factor for improving managerial performance. This study has several limitations.…”
Section: Discussionsupporting
confidence: 84%
“…due to different patterns in participatory budgeting in the public sector. Thus, the results of the study do not supportBreaux, et al (2011) andMelek (2009) on the role of mediation. Budget congruence can increase budget goal commitment, while budget goal commitment cannot affect managerial performance, and finally, budget goal commitment cannot mediate the relation between budget congruence and managerial performance.…”
contrasting
confidence: 80%
See 1 more Smart Citation
“…A study on the impact of budget participation on managerial performance via organizational commitment among the top 500 Turkish firms revealed that budget participation and organizational commitment had a significance influence of managerial performance [15]. Budget participation was noted to improve management performance in the surveyed firms.…”
Section: County Government Budgetsmentioning
confidence: 99%
“…Based on the perspective of Locke's goal-setting theory (1968), the development of this research tends to examine parts and ignore the effects of strategies that can support the achievement of good managerial performance. Systems can be implemented well if employees have an effective organizational commitment (Eker, 2008;Ariyani & Sugiyanto, 2020;Nurani & Nilawati, 2016;Simanjuntak, 2018;Sukandar, 2019;Gratitude, 2019). Thus, based on the perspective of goal-setting theory, this study seeks to investigate the moderating effect of affective organizational commitment on the JRI relationship and government managerial performance.…”
Section: A Introductionmentioning
confidence: 99%